Застосування АВС-костингу при калькулюванні собівартості продукції - Маркус, Ольга Віталіївна; Markus, Olha V. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті розкрито особливості застосування ABC-костингу при калькулюванні собівартості продукції. Подано алгоритм визначення собівартості продукції цим методом. Обґрунтовано необхідність упровадження цього методу на вітчизняних підприємствах, виявлено його переваги та недоліки. Розкрито особливості й умови практичного застосування ABC-костингу при калькулюванні собівартості продукції. The article describes features of application ABC-costing in the calculation of production costs. The object of cost accounting method when ABC is a separate activity (function, operation), and the object of calculation – the kind of goods (works, services). Posted algorithm for determining the cost of production by ABC: 1) overhead by grouping activities (functions or operations, the definition of each of these factors work); 2) a media costs for each type; 3) valuation of carrier unit cost by dividing the amount of overhead for each of the quantitative value of the carrier costs; 4) determining production costs by multiplying the unit cost carrier costs on them by activities necessary for the fulfillment of production. Proved that the cost per unit, calculated using this method is a best estimate financial resources consumed as complex allows for alternative ways to determine relationships between production and use of resources. Thus, the necessity of implementation of this method in domestic enterprises, revealed its advantages and disadvantages. The features and terms of practical application of ABC-costing in the calculation of production costs
Application of ABC-costing Calculation of the Cost Products
Keywords: ABC-костинг; ABC-costing; калькулювання; calculating; собівартість; cost